Planning an innovation marathon at an infectious disease conference with results from the International Meeting on Emerging Diseases and Surveillance 2016 Hackathon. (December 2017) - Ramatowski, John W.; Lee, Christopher Xiang; Mantzavino, Aikaterini; Ribas, João; Guerra, Winter; Preston, Nicholas D.; Schernhammer, Eva; Madoff, Lawrence C.; Lassmann, Britta
Graphical abstract: Six steps of the hackathon model. Step 1 – Participants pitch a problem they are interested in solving during the event. Step 2 – Attendees self assemble into teams with skills necessary to solve the pitched problems. Step 3 – Teams develop potential solutions. Step 4 – Mentors give teams feedback and guidance during prototype creation. Step 5 – Teams present prototyped projects to audience and judges to determine awards. Step 6 – Providing additional resources and communication platforms to allow team collaboration in the post-event environment. Figure developed by paper authors and may be reused with proper citation. Highlights: Hackathon at infectious disease meeting. Interdisciplinary collaboration. Novel solutions. Abstract: A hackathon is best described as an 'innovation marathon'. Derived from the words 'hacking' and 'marathon', it brings together multidisciplinary teams to collaborate intensely over a short period of time to define a problem, devise a solution, and design a working prototype. International scientific meetings are conducive to successful hackathons, providing an audience of expert professionals who describe challenges and ensure the proposed solutions address end-user needs. Collaborations with local organizations and academic centers are crucial to attracting complementary specialties such as IT advisors, engineers, and entrepreneurs to develop sustainable projects. The core process of first identifying and deconstructing a problem followed by solution iteration is applicable to challenges at workplaces around the world. Ultimately, this model can be used to drive innovation and catalyze change in the global health community. The planning, execution, and outcomes of a hackathon event organized in conjunction with the International Meeting on Emerging Diseases and Surveillance (IMED 2016) are described in this article. Physicians, public health practitioners, veterinarians, IT professionals, engineers, and entrepreneurs came together for 2 days to develop solutions at the intersection of emerging infectious diseases and climate change. Projects that resulted from the IMED 2016 Hackathon included environmental impact assessment software for humanitarian organization relief efforts; enhanced communication tools to prevent disease outbreaks; a participatory mobile application to speed the elimination of rabies in Indonesia; integrated disease surveillance platforms; and an improved search function for infectious disease outbreak reports in the ProMED-mail network.